Description of gouty arthritis in the elderly at the Pasar Kuok Batang Kapas health center - Yuliza Birman; Nancy Claudea Pachuary; Budi Yulhasfi Febrianto (Institute of Computer Science (IOCS), 2023)
Gout is a type of arthritis that occurs due to increased levels of uric acid in the body. This is due to the body's inability to normally secrete uric acid. The prevalence of gout arthritis in Indonesia is increasing every year. In 2011 it reached 29.35%, in 2012 it was 39.47% and in 2013 it was 45.59%. To describe the incidence of gouty arthritis in the elderly at the Batang Kapas Health Center in 2021. The scope of this research is rheumatology. The research was conducted in June-August 2021. The type of research is descriptive categorical. The affordable population in this study were all elderly people who visited the Pasar Kuok Batang Kapas Health Center in 2021. The sample size was 38 samples using the total sampling technique. Univariate data analysis was presented in the form of a frequency distribution and data processing using the computerized SPSS program IBM version 25.0. Patients with gout arthritis with the most gender were women, namely 21 people (55.3%), the most uric acid levels were high, namely 28 people (73.7%), the highest body mass index was pre-obesity, namely 22 people (57 .9%), and the most common complaint was joint pain, namely 19 people (50%). The majority of gout arthritis patients were female, with high uric acid levels, pre-obesity body mass index, and complaints of joint pain.